Micromagnetic Simulations of Nanoparticles with Varying Amount of Agglomeration - Blachowicz, Tomasz; Grzybowski, Jacek; Ehrmann, Andrea (Macromolecular Symposia)
Magnetic nanoparticles can be used for medical and other purposes, but can also be integrated in polymeric or other nonmagnetic matrices of diverse shapes, for example, thin-films or fibers. In the latter case, it may be important how the magnetic nanoparticles are distributed in the matrix, a topic which is often not taken into account when such composites are investigated experimentally or theoretically. Especially for small magnetic nanoparticles of dimensions allowing coherent reversal, the magnetic properties of such polymer/magnet composites can change drastically in the case of agglomerations. Here, a method is suggested to quantify the influence of nanoparticle distributions inside nonmagnetic matrices. By changing the average distance between nanoparticles of varying diameters between highly distributed particles and perfectly packed clusters, different magnetization dynamics can be modeled by micromagnetic simulations. Here, this process is shown for various magnetic materials and diameter distributions of magnetic nano-spheres and present corresponding micromagnetic simulation results, which underline the importance of taking into account possible magnetic agglomerations in nonmagnetic space.
Keywords: iron; collapse; cross-section; permalloy; spherical coordinates; virtual sphere